Environmental assessment of bioenergy production from microalgae based systems. (15th December 2016) - Shimako, Allan Hayato; Tiruta-Barna, Ligia; Pigné, Yoann; Benetto, Enrico; Navarrete Gutiérrez, Tomás; Guiraud, Pascal; Ahmadi, Aras
Abstract: Microalgae have been studied as a potential alternative raw material and various technologies have been proposed to transform the algal biomass into energy products. In this study, two bioenergy production systems of very different complexities were modelled to assess their environmental efficiencies: a biodiesel system and a biogas system. Biodiesel system used supercritical extraction and transesterification as key processes; to the best of authors' knowledge, there is no previous work analysing the environmental performances of such production system. Cumulative energy demand, Life Cycle Assessment (LCA) and dynamic LCA for climate change were used to evaluate the environmental footprint of the production systems. Conventional systems for electricity, heat and diesel production were considered for comparison. Energy balance showed that the supercritical extraction and drying steps were the most energy consuming unit operations in biodiesel production and further developments of technologies might be envisaged. LCA showed that climate change was the main contributor to impacts on human health and ecosystem quality due to energy consumed in production steps. Also, heat from biogas was the only product that proved to have a satisfactory environmental performance with regard to other conventional production systems. Finally, dynamic climate change evaluation (used for the first time for bio-chemical processes) revealed no carbon sequestration in microalgae system. Graphical abstract: Highlights: Net energy of biodiesel process is negative. Drying and extraction are problematic. Temporal characteristics were evaluated in a life cycle assessment. Biogas from microalgae digestion is an alternative energy resource to fossil fuels. No carbon sequestration was observed when obtaining bioenergy from microalgae.